2020
DOI: 10.1371/journal.pone.0234325
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of criticism and emotional over-involvement in relatives of early psychosis patients

Abstract: Mechanisms underlying the manifestation of relatives' expressed emotion (EE) in the early stages of psychosis are still not properly understood. The present study aimed to examine whether relatives' psychological distress and subjective appraisals of the illness predicted EE dimensions over-and-above patients' poor clinical and functional status. Baseline patient-related variables and relatives attributes comprising criticism, emotional overinvolvement (EOI), psychological distress, and illness attributions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…The high‐EE group at baseline had higher family/carer anxiety levels compared with the low‐EE group at 12 months. This study complimented Hinojosa‐Marqués et al's (2020) finding that relatives' psychological distress and negative emotional representation of the condition (fear, worry, or anger) predicted criticism and EOI at 6 months. Family/carers may not understand the experiences of ARMS individuals when they first enter services and express higher levels of concern (Izon et al, 2019; Izon, Au‐Yeung, & Jones, 2020) and experience perceived loss (Hinojosa‐Marqués, Domínguez‐Martínez, Sheinbaum, et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The high‐EE group at baseline had higher family/carer anxiety levels compared with the low‐EE group at 12 months. This study complimented Hinojosa‐Marqués et al's (2020) finding that relatives' psychological distress and negative emotional representation of the condition (fear, worry, or anger) predicted criticism and EOI at 6 months. Family/carers may not understand the experiences of ARMS individuals when they first enter services and express higher levels of concern (Izon et al, 2019; Izon, Au‐Yeung, & Jones, 2020) and experience perceived loss (Hinojosa‐Marqués, Domínguez‐Martínez, Sheinbaum, et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Parents remain confused, uncertain, worried, and waiting for service involvement (Izon et al, 2019). Hinojosa‐Marqués et al (2020) reported that relatives' anxiety and negative emotional representation of the condition and attributions of blame to the individual predicted EE criticism at baseline, which may be enhanced when they have less SU contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Violence can trigger feelings of fear, anxiety and stress in family members and, consequently, increase attitudes of excessive concern for the FEP patient and contribute to high-EOI. A recent study found that the experience of psychological distress, such as anxiety, by the relatives was associated with high-EOI (Hinojosa-Marqués et al, 2020). From this perspective, a review study pointed out that the EOI attitudes may have the effect of discouraging the patient's abilities, autonomy and self-confidence and, thus, overprotection may, in the long run, result in difficulty for recovery and greater dependence of the patient on its caregiver (Amaresha & Venkatasubramanian, 2012).…”
Section: Effect Of Family Environment Over the Relapses After The First-episode Psychosismentioning
confidence: 99%
“…Authors suggested that the interaction between caregivers' emotional distress and criticism may emerge after the onset of psychosis but not at the Indeed, relatives' levels of anxiety and depression proved to be predictors of critical attitudes in both ARMS and FEP groups. The difference in results between these studies can be explained by cultural differences between the Japanese (Hamaie et al, 2016) and Spanish samples (Domínguez-Martínez et al, 2017;Hinojosa-Marqués et al, 2020). However, more studies are required on the association between EE and relatives' levels of anxiety and depression at the early stages of psychosis to be able to theorize about it.…”
Section: Is Ee Related To Arms Relatives' Psychological Variables?mentioning
confidence: 98%